Soil Moisture Fluctuation on the Gogorancah Cultivation System - M. Yanuar J Purwanto; Ujang Badrudin (Jurnal Keteknikan Pertanian, 1999)
The yield of "Gogorancah" or gora (dry seeding rice cultivatiorl)system is affected by the availability of soil moisture in the root zone during ils growing season. This paper is subjected to evaluate Jluctuation of soil water condition on gora system based on water balance analysis. Different planting schedule makes variation of the soil water fluctuation. Simulation for the best time seeding scheduling for "gora" was done by using 10 types of schedule and the result showed that yield of timeseeding in November 5-th was better yield than yield in October. Throuh field experiment which carried out for this study, it was proved that gora systeni save water at least as much as 250 mm/Ha/season or 2500 m3/Ha/season forthe land preparation water demand. The maximum water saving occured when gora syten~ is applied for November planting schedule which rice was cultivated as rainfed method, however, the yield is better than planting in October.Key word: gogorancah system, planting schedule, water saving.